Remnant epitopes, autoimmunity and glycosylation. - Opdenakker, G; Dillen, C; Fiten, P; Martens, E; Van Aelst, I; Van den Steen, P; Nelissen, I; Starckx, S; Descamps, F; Hu, J; Piccard, H; Van Damme, J; et al. (2006)
The role of extracellular proteolysis in innate and adaptive immunity and the interplay between cytokines, chemokines and proteinases are gradually becoming recognized as critical factors in autoimmune processes. Many of the involved proteinases, including those of the plasminogen activator and matrix metalloproteinase cascades, and also several cytokines and chemokines, are glycoproteins. The stability, interactions with inhibitors or receptors, and activities of these molecules are fine-controlled by glycosylation. We studied gelatinase B or matrix metalloproteinase-9 (MMP-9) as a glycosylated enzyme involved in autoimmunity. In the joints of rheumatoid arthritis patients, CXC chemokines, such as interleukin-8/CXCL8, recruit and activate neutrophils to secrete prestored neutrophil collagenase/MMP-8 and gelatinase B/MMP-9. Gelatinase B potentiates interleukin-8 at least tenfold and thus enhances neutrophil and lymphocyte influxes to the joints. When cartilage collagen type II is cleaved at a unique site by one of several collagenases (MMP-1, MMP-8 or MMP-13), it becomes a substrate of gelatinase B. Human gelatinase B cleaves the resulting two large collagen fragments into at least 33 peptides of which two have been shown to be immunodominant, i.e., to elicit activation and proliferation of autoimmune T cells. One of these two remnant epitopes contains a glycan which is important for its immunoreactivity. In addition to the role of gelatinase B as a regulator in adaptive immune processes, we have also demonstrated that it destroys interferon-beta, a typical innate immunity effector molecule and therapeutic cytokine in multiple sclerosis. Furthermore, glycosylated interferon-beta, expressed in Chinese hamster ovary cells, was more resistant to this proteolysis than recombinant interferon-beta from bacteria. These data not only prove that glycosylation of proteins is mechanistically important in the pathogenesis of autoimmune diseases, but also show that targeting of glycosylated proteinases or the use of glycosylated cytokines seems also critical for the treatment of autoimmune diseases.